2006
DOI: 10.1007/s10811-006-9087-x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary characterisation of the blue-green pigment “marennine” from the marine tychopelagic diatom Haslea ostrearia (Gaillon/Bory) Simonsen

Abstract: Haslea ostrearia is a common marine tychopelagic diatom which has the particularity of synthesizing a blue-green hydrosoluble pigment called "marennine". This pigment, when released into the external medium, is known to be responsible for the colour of oyster gills. Here we present results for main biophysical and biochemical characteristics of pure intra-and extracellular marennine. Tests for chemical determination show that the nature of the two forms of marennine cannot be distinguished and could be related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(89 citation statements)
references
References 27 publications
4
83
1
1
Order By: Relevance
“…The concentrations of marennine were calculated from these spectra by applying the Beer-Lambert's law. The specific extinction coefficients used were those of pure marennine standards in 250 mmol L −1 NaHCO 3, pH 8, determined according to Pouvreau et al (2006b). By this method, marennine concentrations were evaluated as 0.426 g L −1 in CE and at 0.010 g L −1 in BW.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The concentrations of marennine were calculated from these spectra by applying the Beer-Lambert's law. The specific extinction coefficients used were those of pure marennine standards in 250 mmol L −1 NaHCO 3, pH 8, determined according to Pouvreau et al (2006b). By this method, marennine concentrations were evaluated as 0.426 g L −1 in CE and at 0.010 g L −1 in BW.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, little is yet known about the complete structure, synthesis and biological function of marennine (Neuville and Daste 1978;Schubert et al 1995;Tremblin and Robert 1996;Pouvreau et al 2006b). To advance these studies, a reliable and precise method to monitor and quantify marennine routinely is needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown from previous studies (Pouvreau et al, 2006a) that the supernatant obtained from cultures of H. ostrearia is composed of an extracellular form of marennine with a molecular weight of 9893 AE 1 Da, which is actively secreted into the medium, plus some of the intracellular form, with a molecular weight of 10751 AE 1 Da, released after cell death. Because Pouvreau et al (2006a) demonstrated that pH has a bathochromic effect on the absorption spectrum of marennine, we excluded possible artefacts by controlling the pH of the supernatants from the two species before measurement. At pH 8.0, both absorption peaks, in the UV and visible regions, differed between filtered supernatants from the two diatom cultures.…”
Section: Raman Spectroscopy To Discriminate Diatom Blue Pigments and mentioning
confidence: 99%